Pembuatan Media Pembelajaran Interaktif Menggunakan Unity Berbasis Andorid pada Mata Pelajaran Informatika - Adif, Anjjani Mardhika; Wijaya, Indra; Sefriani, Rini (SAFE-Network, 2025)
This study aims to analyze the validity, practicality and effectiveness of Interactive Learning Media Using Unity Based on Android in Informatics Subjects for Class X at SMKN 9 Padang. This study uses a research and development (R&D) method, using the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were 35 students of class X majoring in Culinary 4. The results of the study showed that the overall validity test by experts on interactive learning media based on Android using Unity for class X at SMK Negeri 9 Padang was 91.03%, so the level of validity can be interpreted as very valid to use. The overall practicality test assessment of interactive learning media based on Android using Unity for class X at SMK Negeri 9 Padang was 89.44%, so the level of practicality can be interpreted as very practical to use. The overall effectiveness test assessment of android-based interactive learning media using Unity for class X at SMK Negeri 9 Padang was 88.12%, so the level of effectiveness can be interpreted as very effective to use. The conclusion of this study is to produce an interesting and useful android-based interactive learning media application for teachers and students both during face-to-face or online learning.